Human resource development : critical perspectives and practices - Bierema, Laura L. (Laura Lee), 1964-; Callahan, Jamie L.; Elliott, Carole, 1966- (Routledge, 2024)
"Human Resource Development: Critical Perspectives and Practices is a landmark textbook on HRD scholarship and practice and is a significant departure from the standard HRD texts available. Based on Bierema and Callahan's (2014) framework for critical human resource development, this book develops an understanding of HRD that addresses both key and contested, issues of practice associated with relating, learning, changing, and organizing for organizations. This book covers the basic tenets of HRD, interrogates the dominant paradigms and practices of the field, teaches readers how to critically assess HRD practices and outcomes, and provides critical alternatives to practice. The text also addresses HRD as a contested practice and the importance for HRD professionals to reflect on their values, maintain their sanity, and retain their employment while attempting to do this difficult work that serves multiple stakeholders. The text weaves in Notes from the World of HRD from international academics and practitioners, giving readers an insight into HRD issues across the globe. This critical text offers an exciting alternative to the instrumentalist, managerialist and masculine perspective of other books. Designed for students and practitioners, this textbook will be essential reading for upper-level courses on human resource development, human resource management and adult education"--